Pengaruh Budaya Organisasi, Motivasi, dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT. Berlian Cahaya Bima Kota Mataram - Sami’un, Sami’un; Hanna, Fermatika Oktavia (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Human resources are one of the key factors to get the best performance, because HR is an effective and efficient factor in determining and achieving goals. Employee performance is the result of work achieved by an employee in carrying out tasks in accordance with the responsibilities given to him. Basically, humans or someone who is in organizational life tries to determine and form an activity plan for all parties, so that carrying out activities does not conflict with the attitudes and behavior of each individual. The population in this study are employees of PT. Berlian Cahaya Bima, which is located at Jalan Selaparang Number 36, Mayura, Cakranegara District, Mataram City, has 120 employees. This study uses a known population and the sample used in this study is a minimum of 100 people. One of the samples taken was proportionate random sampling because the total population was known as 35 employees of PT. Bima Light Diamond. The type of data used is interval data, where the numbers start from the smallest to the largest scale and have the same distance from one another. While the data source used is primary by way of distributing questionnaires to respondents. The results of this study indicate that: 1) organizational culture has a significant influence on motivation, which means that the company pays close attention to each employee's work, so that employees are always given support from the company when doing work; 2) motivation has a significant effect on job satisfaction, which means that the motivation given by the company has a positive effect on employees, so that employees are enthusiastic at work; 3) organizational culture does not have a significant effect on job satisfaction, because job satisfaction is a (positive) attitude of employees towards their work that arises based on an assessment of the work situation; and 4) organizational culture does not have a significant effect on employee performance, employees work based on the organizational culture adopted by the company, if organizational culture encounters obstacles that are happening to employees, then employee performance can be affected. Based on the results of research and processing of data obtained through distributing questionnaires to respondents as many as 150 questionnaires about the influence of organizational culture, motivation, and job satisfaction on employee performance. The results of the evaluation of the goodness of fit indices on the structural model of the research results show good results.